Current status of research and gaps in knowledge of geophagic practices in Africa - Davies, Theophilus C. (Frontiers in Nutrition, 2023)
This article synthesises current knowledge and identifies research gaps on the still intriguing aspects of the subject of geophagy as practised in Africa. Despite the voluminous research literature that exists on the subject, geophagy in Africa is still a largely misunderstood phenomenon. An updated critical review of human geophagy in Africa -with a section on (other) animal geophagy -, highlights several aspects of the practice that need further research. A comprehensive bibliography is assembled, comprising some of the more pertinent and recently published papers (mostly post-dating the year 2005), as well as older seminal works, providing a baseline and robust framework for aiding the search process of Medical Geology researchers and those from allied fields wanting to explore the still poorly understood aspects of geophagy in Africa.